A Comparison Between Cytological and Histopathological Grading System in Cases of Breast Malignancy - Goswami, Alpeshpuri P; Gondaliya, Jignesh V; Shah, Shaila N (Annals of Pathology and Laboratory Medicine, 2020)
Background Treatment of breast malignancies depends on its types and grades. Classification of breast lesion is usually based on the histological appearance of tissue in the tumor. Like histopathology, the diagnostic cytology is also a useful tool for the oncologist and surgeons. It is possible to grade breast cancer on fine-needle aspirates. Material and methods: A prospective study of FNAC of breast lesions was carried out along with its histopathological correlation. Malignant breast lesion diagnosed on FNAC were graded using Robinson's grading system and correlated with Elstons modified Bloom Richardson histological grading system. Results: The sensitivity, specificity and accuracy of the fine needle aspiration cytology to diagnose breast malignancy were 84.84%, 100.00% and 93.75% respectively. Out of 17 cases of Robinson gradeing on FNAC, 12(70.59%) cases were well correlated with Bloom-Richardson histological grade. Conclusion: Cytological grading is simple, less time consuming and with rare exceptions correlates precisely with the histological grade. It helps to know prognostic evaluation of breast carcinoma along with diagnosis.